2.2.52 Problems 5101 to 5200

Table 2.105: Main lookup table. Sorted sequentially by problem number.

#

ODE

CAS classification

Solved?

time (sec)

5101

\[ {}x y y^{\prime }+1+y^{2} = 0 \]

[_separable]

2.422

5102

\[ {}x y y^{\prime } = x +y^{2} \]

[[_homogeneous, ‘class D‘], _rational, _Bernoulli]

2.515

5103

\[ {}x y y^{\prime }+x^{2}+y^{2} = 0 \]

[[_homogeneous, ‘class A‘], _rational, _Bernoulli]

5.090

5104

\[ {}x y y^{\prime }+x^{4}-y^{2} = 0 \]

[[_homogeneous, ‘class D‘], _rational, _Bernoulli]

2.438

5105

\[ {}x y y^{\prime } = a \,x^{3} \cos \left (x \right )+y^{2} \]

[[_homogeneous, ‘class D‘], _Bernoulli]

3.386

5106

\[ {}x y y^{\prime } = x^{2}-x y+y^{2} \]

[[_homogeneous, ‘class A‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

5.194

5107

\[ {}x y y^{\prime }+2 x^{2}-2 x y-y^{2} = 0 \]

[[_homogeneous, ‘class A‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

3.030

5108

\[ {}x y y^{\prime } = a +b y^{2} \]

[_separable]

2.084

5109

\[ {}x y y^{\prime } = a \,x^{n}+b y^{2} \]

[[_homogeneous, ‘class G‘], _rational, _Bernoulli]

1.885

5110

\[ {}x y y^{\prime } = \left (x^{2}+1\right ) \left (1-y^{2}\right ) \]

[_separable]

2.332

5111

\[ {}x y y^{\prime }+x^{2} \operatorname {arccot}\left (\frac {y}{x}\right )-y^{2} = 0 \]

[[_homogeneous, ‘class A‘], _dAlembert]

8.391

5112

\[ {}x y y^{\prime }+x^{2} {\mathrm e}^{-\frac {2 y}{x}}-y^{2} = 0 \]

[[_homogeneous, ‘class A‘], _dAlembert]

3.165

5113

\[ {}\left (1+x y\right ) y^{\prime }+y^{2} = 0 \]

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.532

5114

\[ {}x \left (1+y\right ) y^{\prime }-\left (1-x \right ) y = 0 \]

[_separable]

1.324

5115

\[ {}x \left (1-y\right ) y^{\prime }+\left (x +1\right ) y = 0 \]

[_separable]

1.431

5116

\[ {}x \left (1-y\right ) y^{\prime }+\left (1-x \right ) y = 0 \]

[_separable]

1.430

5117

\[ {}x \left (2+y\right ) y^{\prime }+a x = 0 \]

[_quadrature]

0.819

5118

\[ {}\left (2+3 x -x y\right ) y^{\prime }+y = 0 \]

[_rational, [_1st_order, ‘_with_symmetry_[F(x)*G(y),0]‘], [_Abel, ‘2nd type‘, ‘class B‘]]

1.132

5119

\[ {}x \left (4+y\right ) y^{\prime } = 2 x +2 y+y^{2} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

4.036

5120

\[ {}x \left (a +y\right ) y^{\prime }+b x +c y = 0 \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

0.872

5121

\[ {}x \left (a +y\right ) y^{\prime } = y \left (B x +A \right ) \]

[_separable]

1.400

5122

\[ {}x \left (x +y\right ) y^{\prime }+y^{2} = 0 \]

[[_homogeneous, ‘class A‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

6.346

5123

\[ {}x \left (x -y\right ) y^{\prime }+y^{2} = 0 \]

[[_homogeneous, ‘class A‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

37.352

5124

\[ {}x \left (x +y\right ) y^{\prime } = x^{2}+y^{2} \]

[[_homogeneous, ‘class A‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

3.503

5125

\[ {}x \left (x -y\right ) y^{\prime }+2 x^{2}+3 x y-y^{2} = 0 \]

[[_homogeneous, ‘class A‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

4.844

5126

\[ {}x \left (x +y\right ) y^{\prime }-y \left (x +y\right )+x \sqrt {x^{2}-y^{2}} = 0 \]

[[_homogeneous, ‘class A‘], _dAlembert]

4.005

5127

\[ {}\left (a +\left (x +y\right ) x \right ) y^{\prime } = b \left (x +y\right ) y \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.213

5128

\[ {}x \left (y+2 x \right ) y^{\prime } = x^{2}+x y-y^{2} \]

[[_homogeneous, ‘class A‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

4.771

5129

\[ {}x \left (4 x -y\right ) y^{\prime }+4 x^{2}-6 x y-y^{2} = 0 \]

[[_homogeneous, ‘class A‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

7.241

5130

\[ {}x \left (x^{3}+y\right ) y^{\prime } = \left (x^{3}-y\right ) y \]

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

3.549

5131

\[ {}x \left (2 x^{3}+y\right ) y^{\prime } = \left (2 x^{3}-y\right ) y \]

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

3.822

5132

\[ {}x \left (2 x^{3}+y\right ) y^{\prime } = 6 y^{2} \]

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

3.730

5133

\[ {}y \left (1-x \right ) y^{\prime }+x \left (1-y\right ) = 0 \]

[_separable]

1.255

5134

\[ {}\left (x +a \right ) \left (x +b \right ) y^{\prime } = x y \]

[_separable]

1.459

5135

\[ {}2 x y y^{\prime }+1-2 x^{3}-y^{2} = 0 \]

[_rational, _Bernoulli]

1.489

5136

\[ {}2 x y y^{\prime }+a +y^{2} = 0 \]

[_separable]

1.691

5137

\[ {}2 x y y^{\prime } = a x +y^{2} \]

[[_homogeneous, ‘class G‘], _rational, _Bernoulli]

1.290

5138

\[ {}2 x y y^{\prime }+x^{2}+y^{2} = 0 \]

[[_homogeneous, ‘class A‘], _exact, _rational, _Bernoulli]

4.397

5139

\[ {}2 x y y^{\prime } = x^{2}+y^{2} \]

[[_homogeneous, ‘class A‘], _rational, _Bernoulli]

8.089

5140

\[ {}2 x y y^{\prime } = 4 x^{2} \left (2 x +1\right )+y^{2} \]

[_rational, _Bernoulli]

4.047

5141

\[ {}2 x y y^{\prime }+x^{2} \left (a \,x^{3}+1\right ) = 6 y^{2} \]

[_rational, _Bernoulli]

1.398

5142

\[ {}\left (3-x +2 x y\right ) y^{\prime }+3 x^{2}-y+y^{2} = 0 \]

[_exact, _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.594

5143

\[ {}x \left (x -2 y\right ) y^{\prime }+y^{2} = 0 \]

[[_homogeneous, ‘class A‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

14.735

5144

\[ {}x \left (x +2 y\right ) y^{\prime }+\left (2 x -y\right ) y = 0 \]

[[_homogeneous, ‘class A‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

67.845

5145

\[ {}x \left (x -2 y\right ) y^{\prime }+\left (2 x -y\right ) y = 0 \]

[[_homogeneous, ‘class A‘], _exact, _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

4.871

5146

\[ {}x \left (1+x -2 y\right ) y^{\prime }+\left (1-2 x +y\right ) y = 0 \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.475

5147

\[ {}x \left (1-x -2 y\right ) y^{\prime }+\left (2 x +y+1\right ) y = 0 \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.416

5148

\[ {}2 x \left (2 x^{2}+y\right ) y^{\prime }+\left (12 x^{2}+y\right ) y = 0 \]

[[_homogeneous, ‘class G‘], _exact, _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

2.947

5149

\[ {}2 \left (x +1\right ) y y^{\prime }+2 x -3 x^{2}+y^{2} = 0 \]

[_exact, _rational, _Bernoulli]

1.799

5150

\[ {}x \left (2 x +3 y\right ) y^{\prime } = y^{2} \]

[[_homogeneous, ‘class A‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

4.274

5151

\[ {}x \left (2 x +3 y\right ) y^{\prime }+3 \left (x +y\right )^{2} = 0 \]

[[_homogeneous, ‘class A‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

7.905

5152

\[ {}\left (3+6 x y+x^{2}\right ) y^{\prime }+2 x +2 x y+3 y^{2} = 0 \]

[_exact, _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.408

5153

\[ {}3 x \left (x +2 y\right ) y^{\prime }+x^{3}+3 y \left (y+2 x \right ) = 0 \]

[_exact, _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.529

5154

\[ {}a x y y^{\prime } = x^{2}+y^{2} \]

[[_homogeneous, ‘class A‘], _rational, _Bernoulli]

5.334

5155

\[ {}a x y y^{\prime }+x^{2}-y^{2} = 0 \]

[[_homogeneous, ‘class A‘], _rational, _Bernoulli]

5.116

5156

\[ {}x \left (a +b y\right ) y^{\prime } = c y \]

[_separable]

1.564

5157

\[ {}x \left (x -a y\right ) y^{\prime } = y \left (y-a x \right ) \]

[[_homogeneous, ‘class A‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

4.819

5158

\[ {}x \left (x^{n}+a y\right ) y^{\prime }+\left (b +c y\right ) y^{2} = 0 \]

[_rational, [_1st_order, ‘_with_symmetry_[F(x)*G(y),0]‘], [_Abel, ‘2nd type‘, ‘class C‘]]

4.508

5159

\[ {}\left (1-x^{2} y\right ) y^{\prime }+1-x y^{2} = 0 \]

[_exact, _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.274

5160

\[ {}\left (1-x^{2} y\right ) y^{\prime }-1+x y^{2} = 0 \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

2.063

5161

\[ {}x \left (1-x y\right ) y^{\prime }+\left (1+x y\right ) y = 0 \]

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.819

5162

\[ {}x \left (2+x y\right ) y^{\prime } = 3+2 x^{3}-2 y-x y^{2} \]

[_exact, _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.606

5163

\[ {}x \left (2-x y\right ) y^{\prime }+2 y-x y^{2} \left (1+x y\right ) = 0 \]

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class C‘]]

2.651

5164

\[ {}x \left (3-x y\right ) y^{\prime } = y \left (x y-1\right ) \]

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

2.112

5165

\[ {}x^{2} \left (1-y\right ) y^{\prime }+\left (1-x \right ) y = 0 \]

[_separable]

1.574

5166

\[ {}x^{2} \left (1-y\right ) y^{\prime }+\left (x +1\right ) y^{2} = 0 \]

[_separable]

1.704

5167

\[ {}\left (x^{2}+1\right ) y y^{\prime }+x \left (1-y^{2}\right ) = 0 \]

[_separable]

3.579

5168

\[ {}\left (-x^{2}+1\right ) y y^{\prime }+2 x^{2}+x y^{2} = 0 \]

[_rational, _Bernoulli]

1.734

5169

\[ {}2 x^{2} y y^{\prime } = x^{2} \left (2 x +1\right )-y^{2} \]

[[_homogeneous, ‘class D‘], _rational, _Bernoulli]

2.287

5170

\[ {}x \left (1-2 x y\right ) y^{\prime }+y \left (1+2 x y\right ) = 0 \]

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.896

5171

\[ {}x \left (1+2 x y\right ) y^{\prime }+\left (2+3 x y\right ) y = 0 \]

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

10.959

5172

\[ {}x \left (1+2 x y\right ) y^{\prime }+\left (1+2 x y-x^{2} y^{2}\right ) y = 0 \]

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class C‘]]

2.505

5173

\[ {}x^{2} \left (x -2 y\right ) y^{\prime } = 2 x^{3}-4 x y^{2}+y^{3} \]

[[_homogeneous, ‘class A‘], _rational, [_Abel, ‘2nd type‘, ‘class C‘], _dAlembert]

23.272

5174

\[ {}2 \left (x +1\right ) x y y^{\prime } = 1+y^{2} \]

[_separable]

2.626

5175

\[ {}3 x^{2} y y^{\prime }+1+2 x y^{2} = 0 \]

[[_homogeneous, ‘class G‘], _rational, _Bernoulli]

2.260

5176

\[ {}x^{2} \left (4 x -3 y\right ) y^{\prime } = \left (6 x^{2}-3 x y+2 y^{2}\right ) y \]

[[_homogeneous, ‘class A‘], _rational, [_Abel, ‘2nd type‘, ‘class C‘], _dAlembert]

10.541

5177

\[ {}\left (1-x^{3} y\right ) y^{\prime } = x^{2} y^{2} \]

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

2.230

5178

\[ {}2 x^{3} y y^{\prime }+a +3 x^{2} y^{2} = 0 \]

[[_homogeneous, ‘class G‘], _exact, _rational, _Bernoulli]

1.608

5179

\[ {}x \left (3-2 x^{2} y\right ) y^{\prime } = 4 x -3 y+3 x^{2} y^{2} \]

[_exact, _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.537

5180

\[ {}x \left (3+2 x^{2} y\right ) y^{\prime }+\left (4+3 x^{2} y\right ) y = 0 \]

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

6.107

5181

\[ {}8 x^{3} y y^{\prime }+3 x^{4}-6 x^{2} y^{2}-y^{4} = 0 \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

6.407

5182

\[ {}x y \left (b \,x^{2}+a \right ) y^{\prime } = A +B y^{2} \]

[_separable]

3.427

5183

\[ {}3 x^{4} y y^{\prime } = 1-2 x^{3} y^{2} \]

[[_homogeneous, ‘class G‘], _rational, _Bernoulli]

2.563

5184

\[ {}x^{7} y y^{\prime } = 2 x^{2}+2+5 x^{3} y \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.062

5185

\[ {}y y^{\prime } \sqrt {x^{2}+1}+x \sqrt {1+y^{2}} = 0 \]

[_separable]

2.871

5186

\[ {}\left (1+y\right ) y^{\prime } \sqrt {x^{2}+1} = y^{3} \]

[_separable]

2.346

5187

\[ {}\left (\operatorname {g0} \left (x \right )+y \operatorname {g1} \left (x \right )\right ) y^{\prime } = \operatorname {f0} \left (x \right )+\operatorname {f1} \left (x \right ) y+\operatorname {f2} \left (x \right ) y^{2}+\operatorname {f3} \left (x \right ) y^{3} \]

[[_Abel, ‘2nd type‘, ‘class C‘]]

4.717

5188

\[ {}y^{2} y^{\prime }+x \left (2-y\right ) = 0 \]

[_separable]

1.310

5189

\[ {}y^{2} y^{\prime } = x \left (1+y^{2}\right ) \]

[_separable]

1.405

5190

\[ {}\left (x +y^{2}\right ) y^{\prime }+y = b x +a \]

[_exact, _rational]

1.312

5191

\[ {}\left (x -y^{2}\right ) y^{\prime } = x^{2}-y \]

[_exact, _rational]

1.222

5192

\[ {}\left (x^{2}+y^{2}\right ) y^{\prime }+x y = 0 \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

5.369

5193

\[ {}\left (x^{2}+y^{2}\right ) y^{\prime } = x y \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

3.401

5194

\[ {}\left (x^{2}-y^{2}\right ) y^{\prime } = 2 x y \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

4.789

5195

\[ {}\left (x^{2}-y^{2}\right ) y^{\prime }+x \left (x +2 y\right ) = 0 \]

[[_homogeneous, ‘class A‘], _exact, _rational, _dAlembert]

94.379

5196

\[ {}\left (x^{2}+y^{2}\right ) y^{\prime }+2 x \left (y+2 x \right ) = 0 \]

[[_homogeneous, ‘class A‘], _exact, _rational, _dAlembert]

4.727

5197

\[ {}\left (1-x^{2}+y^{2}\right ) y^{\prime } = 1+x^{2}-y^{2} \]

[[_1st_order, _with_linear_symmetries], _rational]

1.141

5198

\[ {}\left (a^{2}+x^{2}+y^{2}\right ) y^{\prime }+2 x y = 0 \]

[_exact, _rational, [_1st_order, ‘_with_symmetry_[F(x)*G(y),0]‘]]

1.049

5199

\[ {}\left (a^{2}+x^{2}+y^{2}\right ) y^{\prime }+b^{2}+x^{2}+2 x y = 0 \]

[_exact, _rational]

1.279

5200

\[ {}\left (x +x^{2}+y^{2}\right ) y^{\prime } = y \]

[_rational]

1.189